Intradermal administration of hepatitis B vaccine in infants and preschool children - Kurugöl, Zafer; Egemen, Ayten; Erensoy, Selda; Bilgiç, Altınay; Kütükçüler, Necil (The Turkish Journal of Pediatrics, 1997)
One of the ways to administrate hepatitis B vaccination is the intradermal (id) route. The aim of this study is to evaluate the immunologic response of various age groups of children who received three 2 µg id doses of recombinant hepatitis B vaccine. One hundred and eighty-seven children (86 infants, 101 preschool children) were administered a 2 µg dose of recombinant hepatitis B vaccine (Gen Hevac B) intradermally zero, one and six months. Eight weeks after the third vaccination, the geometric mean titers (GMT) of antibody to hepatitis B surface antigen (anti-HBs) of infants was 753 IU/L; that of preschool children was 799 IU/L. There was no statistically significant difference between the anti-HBs GMT of infants and preschool children. However, infants were less likely to have developed protective anti-HBs (≤ 10 IU/L) than preschool children (93% vs 100%, p = 0.009). In 8.1 percent of infants and 3.9 percent of preschool children, local reactions were observed. The 2 µg recombinant vaccine by id route is safe and suitable for immunization of preschool children. The id route is technically difficult to administrate in infants and protective seroconversion rates are lower than in preschool children.
Keywords: intradermal hepatitis B vaccine; infant; preschool children